Taxonomic study on new-record genus Bambusana Anufriev (Hemiptera: Cicadellidae: Deltocephalinae) in China - Dai, Wu; Zhang, Yalin (Zootaxa, 2006)
The species of Bambusana Anufriev, 1969 from China are studied, and two new species, B. fopingensis sp. nov. and B. multidentata sp. nov., are described as new. Both the genus and its type species, B. bambusae (Matsumura, 1914), are reported for the first time from China. The type and other material are deposited separately in the Institute of Zoology, Chinese Academy of Sciences (IZCAS) and Entomological Museum of Northwest A&F University (EM), which are indicated under each species.